2001
DOI: 10.1021/la010388r
|View full text |Cite
|
Sign up to set email alerts
|

Synchronized Self-Motion of Two Camphor Boats

Abstract: The synchronized self-motion of two camphor boats was investigated on a circular water route. Two kinds of synchronization, phase-locking and phase-oscillatory modes, could be produced by changing the temperature, the radius of the circular cell, and the mass of each boat. The nature of the synchronization is discussed in relation to the distribution of the camphor layer, which is an important factor in the driving force of self-motion. The essential features of synchronized motion were reproduced by a numeric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
143
0
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 116 publications
(145 citation statements)
references
References 25 publications
1
143
0
1
Order By: Relevance
“…20 Recently, we reported that the nature of the self-motion of a camphor scraping changes depending on both the internal conditions (e.g., scraping morphology and chemical structure of the camphor derivative) [21][22][23][24] and external conditions (e.g., temperature, surface tension, and the shape of the cell), [24][25][26][27][28] and the essential features of self-motion could be reproduced by a computer simulation. [21][22][23][24][25][26][27][28] In one of these studies, we reported that the mode of self-motion of a camphoric acid boat characteristically changes depending on the concentration of phosphate ion or pH in the aqueous phase, and that the characteristic mode-change between uniform, oscillatory, and no motion is coupled with the acid -base reaction. 22 In this study, we investigated the nature of self-motion depending on the reaction order of the acid-base reaction.…”
Section: Introductionmentioning
confidence: 99%
“…20 Recently, we reported that the nature of the self-motion of a camphor scraping changes depending on both the internal conditions (e.g., scraping morphology and chemical structure of the camphor derivative) [21][22][23][24] and external conditions (e.g., temperature, surface tension, and the shape of the cell), [24][25][26][27][28] and the essential features of self-motion could be reproduced by a computer simulation. [21][22][23][24][25][26][27][28] In one of these studies, we reported that the mode of self-motion of a camphoric acid boat characteristically changes depending on the concentration of phosphate ion or pH in the aqueous phase, and that the characteristic mode-change between uniform, oscillatory, and no motion is coupled with the acid -base reaction. 22 In this study, we investigated the nature of self-motion depending on the reaction order of the acid-base reaction.…”
Section: Introductionmentioning
confidence: 99%
“…The self-motion of a camphor fragment at an air/water interface is driven by the heterogeneous distribution of the camphor molecular layer that develops from the solid fragment [18][19][20][21][22][23][24][25]. That is, the concentration of a camphor layer at a concave area of the camphor fragment is generally higher than that at a convex one; therefore the heterogeneous density distribution of a camphor layer due to the shape of a camphor fragment determines the direction of motion [18].…”
Section: Introductionmentioning
confidence: 97%
“…In the last decade, motions of surfactant particles, almost undeformable droplets, and that of "camphor boats" as well, have been investigated by means of mathematical modelling under certain conditions [14,20,21]. As mentioned above, they can explain the spontaneous symmetry breaking and many other phenomena, such as oscillatory motions in a linear chamber [13] and jamming in an annular channel [22][23][24].…”
Section: Introductionmentioning
confidence: 99%